Electrospraying method for fabrication of essential oil loaded-chitosan nanoparticle delivery systems characterized by molecular, thermal, morphological and antifungal properties - Yilmaz, Mustafa Tahsin; Yilmaz, Azime; Akman, Perihan Kubra; Bozkurt, Fatih; Dertli, Enes; Basahel, Abdulrahman; Al-Sasi, Basil; Taylan, Osman; Sagdic, Osman (ELSEVIER SCI LTD, 2019)
Fabrication of essential oil loaded-chitosan nanoparticles using electrospraying technique appears to be a novel strategy to develop thermally stable nanoparticles possessing higher encapsulation efficiency and particle stability. This study aims to fabricate chitosan nanoparticles (CNPs) loaded with Origanum vulgare essential oil (OEO, Origanum vulgare L.) at different proportions (OEO/CH proportions of 0:1, 0.0625:1, 0.125:1, 0.25:1 and 0.5:1 mL/g) using electrospraying technique. The CNPs were characterized in term of their particle size and stability (dynamic light scattering), encapsulation efficiency (spectrophotometry), and molecular (Fourier transform infrared spectroscopy), thermal (differential scanning calorimetry/thermogravimetric analysis), morphological (scanning electron microscopy) and antifungal (agar dilution method) and fungistatic activity properties. The average particle sizes of the CNPs ranged between 290 and 483 nm with a spherical morphology. Positively charged surface characteristics were observed to increase with the increment of OEO concentration in CNPs. The encapsulation efficiency values were determined in the range of 70.1 and 79.6%. The molecular and thermal analyses exposed very decent encapsulation of OEO into thermally stable chitosan nanoparticles. Morphological analysis verified the spherical shapes of these nanoparticles. Above all, the antifungal effectiveness of OEO against the Alternaria alternates AY1 could be significantly (p < 0.05) increased by its encapsulation into chitosan nanoparticles fabricated by the electrospraying technique. Consequently, it can be stated that the electrospraying technique developed is able to fabricate thermally stable nanoparticles owning higher encapsulation efficiency and particle stability. The results and findings suggest that the electrospraying technique would be a promising method to fabricate chitosan-based nanoparticles as an antimicrobial agent to control their release in a prolonged preservative effect in cosmetic, pharmaceutical and food applications for adjustable dosage forms. Industrial relevance: The fungal agents such as Alternaria alternata cause great damages on post-harvest fresh fruits and vegetables, thus leading to a great economical lose. Therefore, a great variety of methods in struggling with disease have been previously proposed. Nowadays, the most effective leading methods to struggle against plant diseases are those applied with synthetic fungicides to minimize such lose in post-harvest fruit and vegetables. However, intensive and unconscious use of the fungicides leads the pathogens to develop resistance against these agents as well as to accumulation of chemical residues in soil, water and air and finally to formation of carcinogenic effects on human health. Nowadays, a great effort is being exerted to develop novel biodegradable and natural antimicrobial agents for struggling fungal spoilage in postharvest products. Essential oils are among the most widely used natural struggling methods. Essential oils obtained from plants have been extensively used since they are natural antimicrobial agents. However, they cannot be effectively used in spite of their extensive applications. Recently, some researches in the field of nanotechnology have demonstrated that the effectiveness of active substances could be increased by using some techniques. In this respect, we aimed at developing essential-oil-loaded-chitosan-nanoparticle delivery systems using an electrospraying deposition system to prevent fungal colonization on food and plant materials. By increasing antifungal effectiveness of essential oils by their encapsulation into nanoparticles, it will be possible to decrease the levels of regularly applied dose and reflect the obtained outcomes to the food and agriculture industry. This study is the first example of production of essential oil loaded nanoparticles using the electrospraying-hydrodynamic process and showed that encapsulation of oregano essential oil into chitosan based nanoparticles (CNPs) by using the electrospraying deposition technique considerably increased the antifungal effectiveness of the Origanum vulgare essential oil. Our results highlight the potential use of the chitosan nanoparticles (CNPs) loaded with different amounts of Origanum vulgare in food and agriculture industry as an effective fungicidal material against Alternaria alternata, suggesting that the CNPs can be promising tools to compete with synthetic fungicide counterparts and limit use of synthetic ones for struggling of food and plant pathogens. Therefore, the results of this study should be of great importance to industrial applications in terms of development of natural, but effective preservatives as alternative to synthetic ones. In this respect, the CNPs would find a great industrial application area in the food and agriculture industry which seek natural preservatives due to the recent health concerns.
Keywords: Electrospraying technique; Chitosan nanoparticles; Delivery system; Origanum vulgare essential oil; Molecular and antifungal properties; L. ESSENTIAL OIL; ANTIMICROBIAL ACTIVITY; ANTIBACTERIAL; ENCAPSULATION; ANTIOXIDANT; ORIGANUM; STABILITY; ACID; NANOENCAPSULATION; COATINGS; Food Science & Technology